Risk factors of in-stent restenosis after carotid angioplasty and stenting: long-term follow-up study - Park, Sangil; Kim, Bum Joon; Choi, Hye-Yeon; Chang, Dae-Il; Woo, Ho Geol; Heo, Sung Hyuk (Frontiers in Neurology, 2024)
Background: After carotid artery angioplasty with stenting (CAS), it is unclear which risk factors are related to long-term outcomes, including in-stent restenosis (ISR). This study aimed to assess the factors associated with restenosis after CAS with a median follow-up of 35.7 months.Patients who underwent CAS from January 2013 to December 2018 were included if they had symptomatic or asymptomatic carotid artery stenosis. The carotid Doppler ultrasonography (CDU) was followed up after the procedure. We defined at least 50% restenosis using the criteria that the internal carotid artery (ICA) peak systolic velocity (PSV) was greater than 224 cm/s or the ICA to common carotid artery PSV ratio was higher than 3.4. The risk factors for ISR were also assessed.Of the 189 patients, 122 had symptomatic carotid artery stenosis, and 67 had asymptomatic carotid artery stenosis. Patients were evaluated by CDU for a median of 35.7 months (interquartile range 19.5 to 70.0). Kaplan-Meier analysis showed that the longest time to ISR was 39 months, and ISR-free was better in the asymptomatic CAS group. In all groups, ISR was independently associated with current smoker (adjusted odds ratio [aOR], 3.425; 95% confidence interval [CI], 1.086 to 10.801) and elevated ICA PSV at baseline (aOR, 1.004; 95% CI, 1.001 to 1.007).Conclusions: Independent risk factors for ISR in the CAS group included current smoking and elevated ICA PSV at baseline. In the symptomatic CAS group, alcohol was independently associated with the ISR. ISR did not occur after 39 months from the CAS procedure in our study patients. Future studies with extended follow-up are necessary to fully understand the long-term outcomes of CAS.